2020
DOI: 10.3389/fmicb.2020.01365
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ceftazidime-Avibactam Susceptibility in KPC-Producing Klebsiella pneumoniae From Patients Without Ceftazidime-Avibactam Use History – A Multicenter Study in China

Abstract: KPC-producing Klebsiella pneumoniae (KPC-KP) is the most widely spread carbapenem-resistant Enterobacteriaceae (CRE) in China. Avibactam is a novel nonβ-lactam β-lactamase inhibitor which is highly active against KPC. Recently, ceftazidimeavibactam (CAZ-AVI) was approved for clinical treatment in China. Here we conducted a retrospective study to examine the antimicrobial susceptibility of CAZ-AVI prior to its usage in China, and evaluated the potential to develop resistance in KPC-KP. CAZ-AVI MICs were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…Gene amplification has been proposed as one of the drivers of heteroresistance. Notably, amplified bla KPC genes have been detected in K. pneumoniae isolates with profound implications for the reduction of pathogens’ susceptibility to carbapenems ( 8 , 9 ). To this date, however, the precise mechanisms underlying carbapenem resistance mediated by bla KPC-2 amplification, particularly from the perspective of carbapenem heteroresistance contributed by unstably amplified bla KPC , remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Gene amplification has been proposed as one of the drivers of heteroresistance. Notably, amplified bla KPC genes have been detected in K. pneumoniae isolates with profound implications for the reduction of pathogens’ susceptibility to carbapenems ( 8 , 9 ). To this date, however, the precise mechanisms underlying carbapenem resistance mediated by bla KPC-2 amplification, particularly from the perspective of carbapenem heteroresistance contributed by unstably amplified bla KPC , remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al showed that the restoration of functional Ompk35 resulted in a 2–4 fold decreased in the MICs of CZA for selected CZA-resistant isolates, indicating that the nonfunctional Ompk35 was related to CZA resistance [ 19 ]. Cui et al reported the same ompk35 and ompk36 gene mutations were detected in reduced CZA susceptible strains and the CZA susceptible strains, which indicated that ompk35/36 mutations only partially contribute to the reduced susceptibility of CZA in the study [ 33 ]. Similarly, we observed that a truncated Ompk35 and a GD insertion at amino acid position 136–137 in Ompk36 in all our isolates, including 4 CZA-resistant isolates and 4 CZA-susceptible isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Nelson et al reported that porins alteration combined with increased bla KPC-3 gene copy number and gene expression can cause CZA resistance [ 22 ]. And the relative bla KPC-2 copy numbers and relative expression of bla KPC-2 in the reduced susceptibility group were significantly higher than those in the susceptibility group [ 19 , 23 , 33 ]. For mutated bla KPC , the report of KPC variants combined with gene expression and copy number is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Avibactam, as the most effective β-lactamase inhibitor [32] , signi cantly increased the activity of ceftazidime and imipenem against KPC-producing K. pneumoniae in vitro, which decreased the MIC90 values of ceftazidime and imipenem more than sixteen-fold. We also identi ed one KPC-2-producing strain exhibited resistant to ceftazidime/ avibactam, with MIC value 16 ug/mL, it might due to OmpK35/36 defects, blaKPC-2 point mutation and high KPC expression [33][34] . We found a phenomenon that deserves special attention, namely, compared with CR-non-hvKP strains, CR-hvKP strains exhibited high level MIC50 values, especially ceftazidime/avibatam, imipenem/avibatam, tigecycline, which are our last line in treating CRKP-infected patients.…”
Section: Discussionmentioning
confidence: 99%